STUDI KOMPARATIF KINERJA KEUANGAN BANK KONVENSIONAL DAN BANK SYARIAH DI INDONESIA PERIODE TAHUN 2020-2021 - Sukma Putri, Ni Made Ayunda; Sudirman, I Made Surya Negara (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
This study compares the financial results of conventional and Islamic banks that were registered in Indonesia the 2020-2021 period. The research population comprises of 43 conventional and sharia banking businesses that are members of the KBMI I. The sample was determined using the basic random sampling approach method and obtained a total of 39 samples consisting of 30 conventional banks and 9 conventional banks. This study uses secondary data in the form of financial statements of banking companies that publish financial performance ratios consisting of LDR, ROA, ROE, CAR, BOPO, NIM, and NPL ratios. The year period for this study was chosen for 2 years, namely in 2020 and 2021. The hypothesis testing in this study used the independent sample t-test and the Mann Whitney u-test. The results of the study showed that there was no difference in the ratios of LDR, ROA, ROE, CAR, BOPO and NPL between conventional banks and Islamic banks in Indonesia, whereas if measured using the NIM ratio there were differences between the financial performance of conventional banks and islamic banks in Indonesia during the period of observation.